Finite Element Analysis and Optimization of Steel Girders with External Prestressing - Abbas, Ali Laftah; Mohammed, Abbas Haraj; khalaf, Raad Dheyab; Abdul-Razzaq, Khattab Saleem (Salehan Institute of Higher Education, 2018)
Optimization is a process through which the best possible values of design variables are achieved under the given of constraints and in accordance to a selected optimization objective function. Steel I-girders have been used widely in different fields, which are generally fabricated by connecting two plate flanges, a flat web and a series of longitudinal or transverse stiffeners together. The use of steel girder with external prestressing has been used in many countries as a means of strengthening bridges. The purpose of this paper is to develop a finite element model for the optimization of a steel girder with external prestressing. The ANSYS finite element software package was used to find the optimum cross section dimension for the steel girder. Two objective functions are considered in this study there are optimization of the strain energy and total volume of the girder. The design variables are the width of top flange, the thickness of top flange, the width of bottom flange, the thickness of bottom flange, the height of the web, the width of the web and area of prestressing tendons. Two type of steel girder are considered there are steel girder without prestressing and steel girder with prestressing. The results for volume minimization shows that the optimum cross section for steel girder with prestressing smaller than for steel girder without prestressing.